Analisis Laporan Keuangan Untuk Menilai Kinerja Keuangan PT. Garuda Daya Pratama Sejahtera (GDPS) - Anggun Preselia; Anggraeni Yunita; Julia (Jurnal EMT KITA, 2023)
The purpose of this study was to evaluate the financial condition of the company and measure the level of liquidity, profitability, solvency, and activity of GDPS. The type of research conducted was quantitative descriptive, and the data source used was the GDPS financial statements for the period 2019-2021. The results of the study showed that PT. GDPS has a good liquidity ratio to pay short-term debts, but cash management needs to be improved. Profitability ratios show that Net Profit Margin and Return on Asset are low but Return on Equity is good. Solvency ratios show high Debt to Asset Ratio and Debt to Equity Ratio values that can increase the risk of debt payment in the future. However, activity ratios show a good ability to utilize assets to achieve company goals.